2018
DOI: 10.1039/c7cp08055g
|View full text |Cite
|
Sign up to set email alerts
|

The ortho-benzyne cation is not planar

Abstract: A recent review on the photoionisation of the CH isomer ortho-benzyne suggests that bands reported in earlier photoelectron spectra might be due to side products or contaminations, while computations raise doubts, whether the cation has a planar geometry. We therefore reinvestigate the photoionisation of ortho-benzyne, generated by pyrolysis from benzocyclobutenedione, by photoion mass-selected threshold photoelectron (ms-TPE) spectroscopy using synchrotron radiation. The experiments are accompanied by a theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 72 publications
1
20
0
Order By: Relevance
“…For a CCSD­(T) calculation of the cation with the geometry being obtained at the ωB97xD level of theory, the diagnostic, which is a measure for the multireference character of a wave function, has a value of 0.16. This indicates that a single-reference method is unable to predict the equilibrium geometry correctly. Further informations are given in the SI. Therefore, we optimized the geometry of 9 + by CASPT2­(10,10)/cc-pVDZ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a CCSD­(T) calculation of the cation with the geometry being obtained at the ωB97xD level of theory, the diagnostic, which is a measure for the multireference character of a wave function, has a value of 0.16. This indicates that a single-reference method is unable to predict the equilibrium geometry correctly. Further informations are given in the SI. Therefore, we optimized the geometry of 9 + by CASPT2­(10,10)/cc-pVDZ.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that a single-reference method is unable to predict the equilibrium geometry correctly. [71][72][73] Further informations are given in the SI. Therefore, we optimized the geometry of 9 + by CASPT2(10,10)/cc-pVDZ.…”
Section: Methodsmentioning
confidence: 99%
“…The formation, characterization, and application of benzynes has fascinated chemists for more than 90 years due to their Kekulé-type diradical structure, special role in combustion and astrochemistry, and great potential in synthetic chemistry. [48][49][50][51][52][53] o-Benzyne was rst proposed as an intermediate in 1927 by Bachmann and Clarke, 54 and IR, [55][56][57][58][59][60][61] microwave, [62][63][64][65][66] NMR, 67,68 and photoelectron [69][70][71][72][73][74] spectra of o-benzynes have been reported in the last half century. A recent report, 75 however, explains that the NMR data 68 of an o-benzyne generated inside of a hemicarcerand do not belong to an o-benzyne inside the molecular cage, but instead, the signals result from a species formed from a reaction of the o-benzyne with the molecular cage.…”
Section: Introductionmentioning
confidence: 99%
“…While the neutral is planar, it has recently been shown that the cation has a twisted C 2 geometry. 200 Benzyne and allyl were in situ-produced from benzocyclobutenedione (1% in argon) and allyliodide (16% in argon), respectively, in a Chen-type pyrolysis reactor. The mass spectra show clean formation of m/z 116, if both reactants are present.…”
Section: Zooming Into Flame Chemistrymentioning
confidence: 99%